INTERNATIONAL LEGAL PROTECTION OF THE RIVER DANUBE - Bugarski, Tatjana; Tubić, Bojan; Pisarić, Milana (Zbornik radova Pravnog fakulteta u Novom Sadu, 2017)
This paper deals with the protection of the river Danube on international level. The most important act in this field is the Convention on cooperation for the protection and sustainable use of the Danube river, which was adopted in Sofia in 1994. It stipulates a system of supervision and cooperation among states. The Contracting Parties to the Convention exchange the available information on the general conditions of the riverine environment within the catchment area of the Danube River, experience gained in the application and operation of the best available techniques and results of research and development, emission and monitoring data, measures taken and planned to be taken to prevent, control and reduce transboundary impact and other issues. The Convention established International Commission for the Protection of the Danube River which deals with the realization of the aims and provisions of this Convention. It elaborates proposals and recommendations addressed to the Contracting Parties.